Legal challenges could delay carbon tax implementation by 3-5 years. - Barthes (Isonomia, 2025)
Legal challenges could delay carbon tax implementation by 3-5 years.
iso-id: iso:argument:u5QZvp2H; sha256: sha256:a176a37c1386de1621590954132573e533d3ed0955401fbaac6d39fac2703ad9